2020
DOI: 10.3390/jfb11020042
|View full text |Cite
|
Sign up to set email alerts
|

Novel Coatings to Minimize Bacterial Adhesion and Promote Osteoblast Activity for Titanium Implants

Abstract: Titanium nitride (TiN) and silicon carbide (SiC) adhesion properties to biofilm and the proliferation of human osteoblasts were studied. Quaternized titanium nitride (QTiN) was produced by converting the surface nitrogen on TiN to a positive charge through a quaternization process to further improve the antibacterial efficiency. The SiC required a nitridation within the plasma chamber of the surface layer before quaternization could be carried out to produce quaternized SiC (QSiC). The antimicrobial activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Although complete prevention of bacterial adhesion on biomaterials is complicated, various efforts have been developed to effectively minimize and control the bacterial adhesion on biomaterial surfaces [ 15 , 20 , 33 , 34 ]. In this way, new coatings have been developed on the surface of titanium to decrease the biofilm [ 6 , 7 , 15 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although complete prevention of bacterial adhesion on biomaterials is complicated, various efforts have been developed to effectively minimize and control the bacterial adhesion on biomaterial surfaces [ 15 , 20 , 33 , 34 ]. In this way, new coatings have been developed on the surface of titanium to decrease the biofilm [ 6 , 7 , 15 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although complete prevention of bacterial adhesion on biomaterials is complicated, various efforts, such as fabricating thin anti-bacterial films or coatings, have been developed to effectively minimize and control the bacterial adhesion biomaterial surface [ 27 , 28 ]. Camargo et al [ 29 ] demonstrated that coatings based on SiC and TiN applied on Ti surfaces were effective against P. gingivalis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…As the surface roughness reduces from the sub-micron scale to the nano-scale level, two phenomena occur -the surface state gradually changes from hydrophobic to hydrophilic and becomes increasingly unfavorable for the adhesion of most bacteria. Second, the anchoring points for bacterial adhesion gradually decrease, weakening the bacterial-surface bonding strength [77,78]. At the same time, the nanometric roughness ensures integrin activation leading to higher osteoblast attachment [79].…”
Section: Dimensional Analysis Of Ch/hamentioning
confidence: 99%
“…The physicochemical properties of an implant surface, including hydrophobicity, surface free energy and roughness are an absolute necessity for selective osteoblast adhesion [77]. As seen in Fig.…”
Section: Osteoblast Adhesion/ Proliferation Studies On Ch/hamentioning
confidence: 99%